Discovering and Developing Research Interests: A Narrative Inquiry into Three Doctoral Students’ Experiences - Keskin, Magdalena (My University, 2023)
The present study implemented a narrative inquiry approach to gain a deeper understanding of how three doctoral students in Türkiye discovered their research interests. Narrative inquiry involves a careful examination of data and subsequent restorying it into chronologically ordered narratives to create an immersive and detailed representation of the participants’ lived experiences. The researcher was also interested in factors which facilitated and hindered the process of developing and sustaining the participants’ interests. Data gathered through in-depth interviews revealed that doctoral students were aware of their research interests prior to beginning their doctoral studies. Their interests had clear connections with their personal experiences and teaching practice. Demanding coursework, lack of necessary equipment and the pressure to publish research articles were found to be detrimental to the development of research interests forcing the students to conduct studies on topics they were not interested in. Finally, supervisors were found to play an essential role in fostering their students’ research interests on condition that they do not infringe on their supervisees’ autonomy and sense of agency.
Keywords: Higher education; research interests; doctoral students; research engagement